The Effect of Motivation and Competence on Employee Performance at BRI Corporate University - Susanti, Febri; Suhardi, Ayidil (LPPM Universitas Bina Bangsa, 2023)
Human resources are part of Islamic teachings, which from the beginning lead to humans to improve their quality of life starting from the development of a culture of intelligence. This study aims to examine the effect of motivation and competence on the performance of BRI Corporate University employees. Sampling using saturated samples as many as 30 employees. The results obtained are motivation and competence on employee performance which affect employee performance at BRI Corporate University